Cell Death in Mammalian Ovary - Vázquez-Nin, Gerardo H. (Springer Netherlands : Imprint: Springer, 2011)
The ovary is a suitable organ for studying the processes of cell death. Cell death was first described in the rabbit ovary (Graaffian follicles), the phenomenon being called ‘chromatolysis’. To date, it is recognized that various forms of cell death (programmed cell death, apoptosis and autophagy) are essential components of ovarian development and function. Programmed cell death is responsable for the ovarian endowment of primordial follicles around birth; in the prepuberal and adult period, apoptosis is a basic mechanism by which oocytes are eliminated by cancer therapies and environmental toxicants; in the ovarian cycle, follicular atresia and luteal regression involve follicular cell apoptosis. Finally, abnormalities in cell death processes may lead to ovarian disease such as cancer and chemoresistance. In this book, after an introductory description of various forms of cell death and of the ovary development and function in mammals, the processes of cell death in ovarian somatic cells and oocytes are described at cytological, physiological and molecular levels and analyzed in the embryonic, prepuberal and adult ovary. A complex array of molecular pathways triggered by extrinsic and intrinsic signals able tor induce or suppress cell death in the same cell, according to cell type and ovary developmental stage, emerges. Physiological interactions with the axis hypothalamus-hypophysis as well as ovarian internal functional signal are also critically reviewed to explain the abortive development of follicles before the beginning of the ovarian cycle. The book conveys information useful to the updating of biologists and physicians who are interested to the ovary biology and functions. Hopefully it should provide also clues for stimulating novel experiments in the study of cell death in the mammalian ovary still at an early stage.